TEACHER ABUSE AND ASSOCIATED SOCIODEMOGRAPHIC VARIABLES IN UNIVERSITY STUDENTS - Ramos rodríguez, Irma (Advances in Social Sciences Research Journal, 2020)
Teacher abuse is an ancient practice at different educational levels, the attacks by teachers vary from verbal and physical abuse, social exclusion, among other forms of abuse. Objective: To analyze the relationship between teacher abuse with gender, age, career, and other associated variables in students of different careers from a public university in Mexico. Methodology: A descriptive, cross-sectional, analytical study was carried out in 1149 first semester university students to collect the information, two questionnaires were applied, one on sociodemographic data and the other on teacher abuse. Results: Teacher abuse was presented in 10.5% of the participants, who claim to have been mistreated by at least one teacher in the current semester, 31.4% say they are afraid of attending university, 9.6% claim to fear a teacher. No differences were found between teacher abuse and the gender of the participants, or according to age, but there were differences according to the degree they were studying. Conclusions: Teacher abuse is a common practice in the university, this can cause in the student fear of teachers, fear of attending the university, absenteeism, school dropout and low academic performance.